Mitochondrial uncoupling and lipid metabolism in adipocytes. (November 2001) - Kopecký, J.; Rossmeisl, M.; Flachs, P.; Bardová, K.; Brauner, P.
Abstract : Metabolism of white adipose tissue is involved in the control of body fat content. In vitro experiments indicated a dependence of lipogenesis on mitochondrial ATP production, as well as a reciprocal link between hormonal effects on metabolism and energetics of adipocytes. Therefore, mitochondrial uncoupling in adipocytes that results in stimulation of energy dissipation and depression of ATP synthesis may contribute to control of lipid metabolism and adiposity. This is supported by the expression of protonophoric proteins in adipocytes, e.g. uncoupling proteins (UCPs) 2 and 5, and some anion transporters, and induction of UCP1 and UCP3 in white fat by pharmacological treatments that reduce adiposity. Negative correlation between expression of UCPs in adipocytes and accumulation of white fat was also found. Expression of UCP1 from the adipose-specific promoter in aP2- Ucp 1 transgenic mice mitigated obesity induced by genetic or dietary factors. The obesity resistance, accompanied by mitochondrial uncoupling in adipocytes and increased energy expenditure, resulted from ectopic expression of UCP1 in white but not in brown fat. Probably due to depression of ATP/ADP ratio in white fat of transgenic mice, both fatty acid synthesis and lipolytic action of noradrenaline in adipocytes were relatively low. These results support the role of protonophoric proteins in adipocytes in the control of adiposity. The main function of these proteins in white fat may be modulation of lipogenesis and intracellular hormone signalling. Augmentation of energy expenditure may be of relatively small importance, in accordance with the low oxidative capacity of white adipocytes.